MPEG-4 multimedia for our time. - Koenen, R. (IEEE spectrum)
The MPEG-4 standard explores every possibility of the digital environment. Recorded images and sounds co-exist with their computer-generated counterparts, a new language for sound promises compact-disk quality at extremely low data rates; and the multimedia content could even adjust itself to suit the transmission rate and quality. Possibly the greatest of the advances made by MPEG-4 is that viewers and listeners need no longer be passive. The height of ?interactivity? in audiovisual systems today is the users ability merely to stop or start a video in progress. MPEG-4 is completely different: it allows the user to interact with objects within the scene, whether they derive from so-called real sources, such as moving video, or from synthetic sources, such as computer-aided design output or computer-generated cartoons. Authors of content can give users the power to modify scenes by deleting, adding, or repositioning objects, or to alter the behavior of the objects. Perhaps the most immediate need for MPEG-4 is defensive. It supplies tools with which to create uniform (and top-quality) audio and video encoders and decoders on the Internet, preempting what may become an unmanageable tangle of proprietary formats. In addition to the Internet, the standard is also designed for low bit-rate communications devices, which are usually wireless